2017
DOI: 10.2174/1566524017666170421151940
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Attenuates LPS-Induced Acute Lung Injury in Mice by Regulating Autophagy and Sirtuin Expression

Abstract: The protective effect of HT on lung inflammation in ALI mice may be attributed to the promotion of autophagy, which is likely associated with the activation of the SIRT/MAPK signaling pathway. Importantly, this study provides new insight into the molecular mechanisms of HT and its therapeutic potential in the treatment of acute respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Consistent with the previous report, we observed that Res up‐regulated the expression of SIRT1, whereas LPS moderately reduced the expression of SIRT1 in BMDMs. The results were consistent with previously reports, in which there was lower SIRT1 expression in the inflammatory lungs of animal models with LPS‐induced ALI and pulmonary contusion . However, our further study indicated that co‐treatment of BMDMs with both Res and LPS prevented the LPS‐induced suppression of SIRT1 (Figure C), demonstrating the important role of Res in activation of SIRT1 signalling.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the previous report, we observed that Res up‐regulated the expression of SIRT1, whereas LPS moderately reduced the expression of SIRT1 in BMDMs. The results were consistent with previously reports, in which there was lower SIRT1 expression in the inflammatory lungs of animal models with LPS‐induced ALI and pulmonary contusion . However, our further study indicated that co‐treatment of BMDMs with both Res and LPS prevented the LPS‐induced suppression of SIRT1 (Figure C), demonstrating the important role of Res in activation of SIRT1 signalling.…”
Section: Discussionsupporting
confidence: 93%
“…The results were consistent with previously reports, in which there was lower SIRT1 expression in the inflammatory lungs of animal models with LPS-induced ALI and pulmonary contusion. [26][27][28] However, our further study indicated that co-treatment of BMDMs with both Res and LPS prevented the LPS-induced suppression of SIRT1 ( Figure 7C) In conclusion, this study indicated that Res suppressed lung inflammation of mice with LPS-induced ALI, in association with significantly reduced neutrophil infiltration and production of F I G U R E 8 Schematic diagram of resveratrol (Res)-mediated suppression of ALI through STAT3/SOCS3 signalling. LPS induces oxidative stress and activates STAT3, subsequently induces IL-6, IL-1beta and CXCL15 expression, ultimately causes ALI/ARDS.…”
Section: Res Suppressed M1 Cell-biased Polarization Of Bmdms From Wmentioning
confidence: 64%
“…Sirt1 has been shown to be essential for synaptic plasticity, cognitive functions [150], modulation of learning, and the preservation of memory processes that deteriorate during aging, in the brain [151]. Recently, in vitro and in vivo studies suggest that HT and OLE inhibit the inflammatory response through different pathways regulated by several members of the sirtuin family (e.g., Sirt1, Sirt2, Sirt6) [140,[152][153][154][155][156].…”
Section: Redox Homeostasis and The Inflammatory Responsementioning
confidence: 99%
“…In the DHM only and DHM + LPS groups, the mice received DHM (500 mg/kg) by gavage once per day for 4 consecutive days prior to the intranasally administration 25 μg of LPS. Twenty‐four hours after LPS administration, the plasma, tissue samples, and bronchoalveolar lavage fluid (BALF) of mice were collected for the experiments as described previously . Before formal experiments, a preexperiment was carried out and we found that DHM at the dose of 500 mg/kg exerts strong protective effects against the lung injury (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Lungs from mice in all groups were removed, embedded, and cut into 7 μm sections. Subsequently, tissue sections were stained with H&E. Semi‐quantitative analyses of inflammatory cell infiltration in lung sections were performed as previously described …”
Section: Methodsmentioning
confidence: 99%